Values preferred by students of the Faculty of Social Sciences of the Jan Kochanowski University’s Branch in Piotrków Trybunalski – in the light of empirical research - Andrzej Felchner; Katarzyna Gal; Kamila Jakubczak-Krawczyńska (Lubelski Rocznik Pedagogiczny, 2017)
Values are the main factor of people’s aspirations and motivations. They are also favourable to creation of man’s self-identity, which is understood as a competence to acting and solving problems. These are the main reasons for values’ leading role in the social life. There is no consensus between authors how to define a value term. Each of them has his/her own idea for describing a value problem. Despite of these discrepancies, the authors of this article take an endeavour to search values preferred by students of the Faculty of Social Sciences of the Jan Kochanowski University’s Branch in Piotrków Trybunalski. This article contains only preliminary conclusions according to our empirical research. The fundamental elaboration is already being prepared. The general results of our research show that values preferred by our respondents are similar to the rest of population. The family is the most important value in our students’ lives. Parents and grandparents have the biggest influence on shaping their values hierarchy. But most of all, our respondents are convinced that being able to relay on oneself, own thoughts and ideas is the most important value in today’s life.